Hierarchy development of safety performance elements and attributes for Malaysia’s low cost housing / Husrul Nizam Husin … [et al.] - Husin, Husrul Nizam; Nawawi, Abdul Hadi; Ismail, Faridah; Khalil, Natasha (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
The general building conditions in low cost housing are part of human's quality indicator. Since the First Malaysia Plan (1966- 1970), there is an emergence development of low-cost housing construction in Malaysia that intentionally acts as an approach to resettle of squatters or illegal residential. However, there are rising issues on the delivery performance of low-cost housing since the occupants are inclined to safety hazards. Evidence shows that safety is a major problem in low cost housing and it is apparent after the building is occupied by the residents. The evaluation of safety hazards, such as structural failures in a high-rise context and quality difunctional, were largely ignored during occupancy period. Therefore, this research suggests a conceptual framework and hierarchy for safety performance elements and attributes to evaluate the performance of low-cost housing. Each safety elements are compiled and collected from literatures and pilot articles to provide the attributes. The framework covers eight (8) elements of safety under the category of building performance and building quality. There are 24 safety attributes that is relatively affect the occupants' safety. This research also conduct further survey to gain validity on the determinants of safety attributes by using experts' judgment via questionnaire survey and interviews.